Utilization of Home Yard for Lettuce Cultivation with a Hydroponic - Ungki Marnando; Widayanti Widayanti; Septilia Septilia; Uswatun Hasanah; Arini Rosa Sinensis (Jurnal Biologi Tropis, 2022)
The development of technology is currently very rapid, especially technological developments in the agricultural sector. However, some farmers do not use the land as an agricultural business. The purpose of the study was to provide a strategy for using yard land as hydroponic lettuce cultivation. This research method is a survey. The research instrument used an open questionnaire, interviews and analyzed descriptively qualitatively. The results showed that vegetable cultivation can be done hydroponically. Vegetables grown hydroponically in this study were lettuce. Planting using a hydroponic system is an environmentally friendly plant process because its cultivation does not require excessive pesticides. In addition, it can take advantage of a narrow land as a planting medium. Further research needs to analyze the types of hydroponic plants that are suitable for each surrounding area